Improving Economic Benefits through Coal Products Optimization in a Given Group - Zhang, Kai; Ji, Changsheng; Ren, Haibing (International Journal of Economics, Business and Management Studies, 2017)
Improving economic benefits from a large coal mining group with several operations is always the first objective of its operator. More concerns are usually focused on the unit operations and their cost. An optimization model for coal products and production rate based on Simplex Method(SM) and Algorithm of Universal Global Optimization(AUGO) approach is established in order to maximize the economic benefits of a given mining group in its existing cost construction. The result shows that the total economic return of the group could be improved a lot through optimization of its coal products and production rather than the summation of its every single mine’s coal products and production rate, each operation of the group should do its best to produce as more as possible high quality products it can produce, and the mines with inferior quality of products should excavate their deposit according to the optimized production rate to make the whole system profit maximum rather than its own designed production.